Do pediatric shoulder fractures benefit from surgery?. Issue 1 (10th February 2021) - Thomson, Jennifer E.; Edobor-Osula, O. Folorunsho
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: We aimed to review considerations, current treatment options, and complications in the management of pediatric proximal humerus fractures. Recent findings: Recent literature has shown an increased incidence of operative management of proximal humerus fractures. With increased age, and increased deformity, studies report excellent outcomes after operative treatment. Still, patients under the age of 12 and with Neer grade I and II fractures are consistently treated nonoperatively. Summary: Indications for operative management of proximal humerus fractures in skeletally immature patients have become increasingly widened. Current literature emphasizes the stratification of patients based on displacement, angulation, and shortening, with overall positive outcomes. Each case should be considered on individual bases, accounting for both radiographic parameters, developmental stages of patients, and potential complications. In the authors' opinion, adolescent patients with Neer Horowitz 3 and 4 fractures surgical management should be considered. In younger patients with nonoperative management, even with significant displacement, is the mainstay of treatment because of the tremendous remodeling potential of the proximal humerus in children. Video abstract: http://links.lww.com/MOP/A56